Pengaruh Pajak Daerah, DBH, dan DAK terhadap Kemandirian Keuangan Pemda di Provinsi Riau - Winarni Rahayu; Asep Syamsu Diyar; Tri Priyatmo (Direktorat Sistem Perbendaharaan, 2024)
This study is analyzing the influences of regional taxes, revenue sharing funds (DBH), and special allocation funds (DAK) on regional financial independence. The samples taken in this research cover all districts and cities in Riau Province for 6 years, specifically in the year 2017 to 2022 used as the panel data. Data obtained from BPK's LHP on Regional Government LKPD (LKPD that has been audited by BPK). This research applies multiple linear regression with a random effect method (REM) model which is processed with the EViews 12 application. The analysis found that regional taxes have a significantly positive influence on regional financial independence. On the other hand, profit sharing funds/DBH and special allocation funds/DAK have a significantly negative influence on regional financial independence. In conclusion, this study demonstrates a clear link between regional revenue sources (taxes, DBH, DAK) and a region's ability to manage its finances independently.